Social cohesion as the missing link between natural resource management and peacebuilding: Lessons from cocoa production in Côte d’Ivoire and Colombia - Löhr, Katharina; Aruqaj, Bujar; Baumert, Daniel; Bonatti, Michelle; Brüntrup, Michael; Bunn, Christian; Castro-Nuñez, Augusto Carlos; Chavez-Miguel, Giovanna; Rio Duque, Martha Lilia del; Hachmann, Samyra; Morales Muñoz, Héctor; Ollendorf, Farnziska; et al. (MDPI, 2021)
Social cohesion plays a key role in processes of peacebuilding and sustainable development. Fostering social cohesion might present a potential to enhance the connection of natural resource management and peacebuilding and better functioning of sustainable land use systems. This contribution explores the nexus between social cohesion, natural resource management, and peacebuilding. Research is based on experience from cocoa production in two post-conflict countries, Côte d’Ivoire and Colombia.